Writing Strategies use: Arabic as a foreign Language in Sri Lankan context - Gafoordeen, N. (My University, 2013)
Research on writing strategy use in Arabic as a foreign language is still in starting point. Few studies have contracted on essay written in Arabic as a final product and illustrated deficiencies that surfaced. This study investigated the writing strategies employed by 6 learners in Fathih institute of Sri Lanka (FISL). Qualitative research conducted through the think aloud protocol; observation and retrospective interview for provide the facts. Performance results on pilot study revealed that proficient learner employed varieties of writing strategies rather than average learner and less proficient learners on their essay writing task. The findings revealed that there is still a lot to be done to improve the Arabic writing skill of Sri Lankan learners. The implications of the results are that, teachers need to rethink about the problems that average and less proficient students were encountered and then try to figure out a way to help them. Also, need to help them how to make their place and organize their opinions more reasonably in writing activities. Keywords: Arabic Language, cognitive, essay, writing strategy, foreign language
Keywords: Writing Strategies use: Arabic as a foreign Language in Sri Lankan context